THE ROLE OF OPERATIONS RESEARCH IN MANAGERIAL DECISION-MAKING - Cvetkoska, Violeta (My University, 2017)
Managers in all organizations should take into account the qualitative aspects of the problem they face, but they should also use the solution of quantitative models as a recommendation in order to make a good decision. The field of Operations Research includes a “buffet breakfast” of analytical methods developed to solve real complex problems and to help make better decisions. Operations Research has been applied in diverse areas, such as: agriculture, aviation, construction, education, electronics, finance, healthcare, manufacturing, military, sports, telecommunications, transportation, etc. Operations Research generates powerful benefits for organizations, such as: increased revenue, increased efficiency, reduced cost, optimized resource use, improved customer service, etc. The aim of the paper is to examine the role of Operations Research in managerial decision-making in renowned organizations around the world. Applications of Operations Research in 30 organizations are presented and the annual savings are given.
Keywords: managerial decision-making, operations research, analytical methods, benefits